Stability of the maxilla and mandible in patients with dentofacial deformities after multi-segmental Le Fort I osteotomy combined with sagittal split ramus osteotomy - Kasahara, Masaki; Hasebe, Daichi; Suda, Daisuke; Sakuma, Hidenobu; Saito, Naoaki; Saito, Daisuke; Nihara, Jun; Kobayashi, Tadaharu (Journal of oral and maxillofacial surgery, medicine, and pathology, 2025)
Skeletal stability after multi-segmental Le Fort I osteotomy combined with sagittal split ramus osteotomy in patients with dentofacial deformities was evaluated using frontal and lateral cephalograms in this study. The subjects were 19 patients (3 males and 16 females) with dentofacial deformities who had undergone multi-segmental Le Fort I osteotomy at our hospital between January 2011 and December 2021. The mean age of the patients at the time of surgery was 27 years (age range: 15–46 years). The patients were classified into skeletal Class II and Class III groups according to the ANB angle determined by lateral cephalometric analysis: Class II (ANB angle> 4), and Class III (ANB angle < 1). Changes in the positions of the maxilla and mandible were analyzed with frontal and lateral cephalograms taken immediately before surgery (T0), a few days after surgery (T1), and one year after surgery (T2). The amount of movement of the maxilla and mandible at surgery varied from case to case. On the other hand, the amount of postoperative change in the maxilla and mandible was about 1 mm in most subjects, suggesting that skeletal stability after multi-segmental Le Fort I osteotomy is quite high. Postoperative maxillary position after MSL1 was stable overall, but postoperative relapse should be carefully controlled in cases with open bite, asymmetry, and/or enlarged maxillary dental arch.